Labour Rights Protection of Foreign Workers After Enactment of Law Number 6 of 2012 in Sidoarjo Regency - Rifqi Ridlo Phahlevy; Mochammad Tanzil Multazam; Noor Fatimah Mediawati (Rechtsidee, 2015)
Enactment of Law No. 6 of 2012 on the Ratification of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, is a manifestation of the government's efforts in human rights, and also the Indonesian government protection measures against the presence of migrant workers in overseas. However, with the passing of this Law, the Government also has an obligation to protect the Foreign Workers who are in Indonesia, to protect their rights as contained in the convention. Sidoarjo Regency is one of the districts with a population of Foreign Workers pretty much in East Java, so Sidoarjo considered to represent ideal conditions most of the local government in Indonesia in terms of a form of protection against TKA after the enactment of Law No. 6 of 2012. This normative law research was supported by primary data sourced from the Social Service Workers at Sidoarjo Regency. Based on research that has been done, founded the lack of regulations Sidoarjo district that specifically regulates the protection of the rights of foreign workers.